Processos de identificação de gênero e transexualidades na era das mídias digitais - Genari, Tayná Ribeiro (2017)
The proposal of this research is to collect and analyze the variability of social representations about transsexuality that circulate on the internet according to the trans people themselves. The research was based on the dynamics of use that trans people make of certain digital media, specifically social networks and blogs, as a source of information, sharing, debate and socialization. Therefore, I used the online observation of blogs, pages/communities of Facebook and Youtube channels, wich are constituted as spaces of circulation of speeches about transsexuality. In dialogue with Queer Theory, Gender studies, and other digital media researches I explore the relationship between representations, corporalities, subjectivities as the transsexuality involve a cultura dynamic which is associated with modes of understand/modify bodies and subjectivities.